Variation in the cervical range of motion over time measured by the "flock of birds" electromagnetic tracking system - Bergman, Gert J D; Knoester, Bianca; Assink, Nienke; Dijkstra, Pieter U; Winters, Jan C (Spine (Philadelphia, Pa. 1976), 2005)
Observational longitudinal study. To establish the normal variation over time for active and passive cervical range of motion (ROM) measured with the Flock of Birds electromagnetic tracking system (FOB). Data about normal variation of cervical ROM over time are scarce but important for the interpretation of study results. Forty-eight subjects without a manifest dysfunction in neck and shoulder region (asymptomatic group) and 58 subjects with a dysfunction in the neck and shoulder region (symptomatic group) participated in this study. Cervical active and passive ROM was assessed in three different sessions 6 weeks apart. The following movements were measured: flexion-extension, lateral bending, and axial rotation in neutral, flexed, and extended position. A wide range of variation of active and passive cervical ROM was found at the 6- and 12-week measurement in the asymptomatic group as well as in the symptomatic group. Highest variation was found during passive ROM testing as compared with active ROM testing. The symptomatic group showed larger variation than the asymptomatic group. Cervical range of motion varies considerably over time. This variation should be taken into account when results of therapeutic trials with respect to cervical ROM are interpreted.